Supply Chain Conceptual Model to Optimize a Local Food Agroindustry from the Coconut Milk Processing - Meilizar Meilizar; Rika Ampuh Hadiguna; Santosa Santosa; Nofialdi Nofialdi (Journal of Applied Engineering and Technological Science (JAETS), 2024)
This study uses a soft system methodology to examine the coconut milk supply chain, which supports the local food agro-industry, particularly for rendang products. It aims to develop a fundamental concept to optimize this supply chain. The proposed method is effective for addressing complex, multi-stakeholder problems. Using systems thinking, real-world system behaviour is converted into a conceptual model, facilitating decision-making through customer, actor, transformation, worldview, owner, and environment components. The findings include a conceptual model translated into a causal loop diagram, part of a dynamic systems approach, which shows the interconnections and feedbacks among variables in the supply chain, such as raw material supply, logistics costs, production volume, and distribution costs. This stage identifies stakeholders and systematically illustrates the relationships in managing the flow of goods. It provides a basis for designing a supply chain network aligned with local government policies for developing the coconut milk agro-industry. It aims to optimize the local food industry, particularly rendang, in West Sumatra province. After creating the conceptual model, gap analysis and validation were conducted, comparing the model with real-world insights from stakeholders, including coconut farmers, producers, rendang manufacturers, academic institutions, and local governments. Validation focused on efficiency, efficacy, and effectiveness. The results demonstrate the foundational idea for designing the coconut milk agro-industry supply chain network to support local food products, as depicted in the causal loop diagram.